(3GdJcedI hGdUdI hGdPjd deG aGJ UGMH GdbGehSs - (3eMeO Hf eMeO Hf eMeO Hf YHO GdQRGb GdMSjfj GdRHjOj, CHh GdajV, GdedbH H oerQnJVi GdnqRpHjpOj , J (B1205 (3g` s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO ajg jHOC CKfGA aUd GdLje eY GdgeRI Hbhdg (B: (3LjC GdLQGO gLe Ydi GdHdO hcd WGdY aLCI s
(3BNQgG (B:s
(3jfJgi HBNQ MQa GdQGA HaUd GdjGA eY GdQGA Hbhdg (B: (3jdHQ cjfUQ CMedg UGMH GdbGehS hgh GHf NWdZ GdaGfjOi GdcQLi CHh efUhQ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI fGbUI GdChd s
Keywords: (3GddZIs